Reasoned decisions in construction contracts evaluation - Mitkus, Sigitas; Trinkūnienė, Eva (Technological and Economic Development of Economy, 2008)
Preparation of an agreement has a great influence on economic success of both parties and on their behaviour in order to increase their profits and to protect themselves against a possible loss. It is important to use technological innovations in construction contracting. Even when the contractor is selected and the price and work terms are negotiated, it is possible to choose several variants of agreements. The aim of this article is to develop a hierarchical model of criteria of a construction contract agreement based on their functions. Construction contract agreements can be concluded, evaluated and compared on the basis of this model. The model forms the basis of decision support system for analysis of construction contracts. Decision support system created on the basis of the presented model can be very useful and helpful in construction contract agreement and can be widely implemented in different construction sectors.Racionalūs sprendimai vertinant statybos rangos sutartisSantrauka. Tinkamas statybos rangos sutarčių parengimas turi didelę įtaką abiejų šalių sutarties įvykdymo ekonominei sėkmei. Netgi tais atvejais, kai statybos rangovas yra jau parinktas, sutarta dėl statybos kainos ir kitų esminių sutarties sąlygų, galimi daugiau negu vienas statybos rangos sutarčių variantai. Siekiant parinkti racionalų sutarties variantą reikia sudaryti statybos rangos sutarties modelį ir paruošti sutarties vertinimo sprendimo paramos sistemą.  Autoriai siūlo statybos rangos sutartis vertinti naudojant hierarchinį statybos rangos sutarties modelį. Straipsnyje aprašyta autorių siūloma internetinė statybos rangos sutarčių vertinimo sistema, pagrįsta pasiūlytu statybos rangos sutarties modeliu.Reikšminiai žodžiai: sprendimų paramos sistemos, statybos rangos sutartys, daugiatikslis vertinimas.First published online: 21 Oct 2010